Options for Accessing Online Electronic Resources in Difficult Fiscal Times. Issue 1 (2nd January 2021) - Hoogland, Margaret A.
Abstract: Accessing electronic books and electronic journals both on- and off-campus is no longer a perk, but rather an expectation of community members. Providing access off-campus is expensive and requires constant monitoring. Further, costs for electronic journals continue to increase and publisher pricing models and products have changed. A 2019 survey of hospital, corporate, and academic librarians showed that libraries plan to continue using the decision-making procedures and policies they created a decade ago. If existing policies and procedures in libraries are not revisited and updated to meet challenges presented by the Digital Age, options for accessing electronic information will diminish.